Coordinated Vehicle-to-Grid Scheduling to Minimize Grid Load Variance - Hashim M.S.; Yong J.Y.; Ramachandaramurthy V.K.; Tan K.M.; Tariq M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Automotive batteries; Charging (batteries); Commercial vehicles; Electric discharges; Electric vehicles; Scheduling; Scheduling algorithms; Vehicle-to-grid; Electric vehicle batteries; Grid-connected; Load leveling; Load profiles; Peak load; Power grids; Residential areas; Electric power transmission networks